Oral health in children and adolescents with juvenile idiopathic arthritis - a systematic review and meta-analysis - Marit S. Skeie; Elisabeth G. Gil; Lena Cetrelli; Annika Rosén; Johannes Fischer; Anne Nordrehaug Åstrøm; Keijo Luukko; Xieqi Shi; Astrid J. Feuerherm; Abhijit Sen; Paula Frid; Marite Rygg; et al. (BMC, 2019)
Abstract Background Observational studies examining the association between oral health and juvenile idiopathic arthritis (JIA) among children and adolescents have reported inconsistent findings. The aims of this systematic review and meta-analysis were to ascertain a potential difference in oral health and oral health-related quality of life (OHRQoL) among children and adolescents with JIA and healthy peers, and to assess the association of prevalence of oral diseases/conditions, temporomandibular disorders (TMD), including temporomandibular joint (TMJ) diseases, in relation to activity and severity of JIA. Method Medline Ovid, Embase, CINAHL, SweMed+ and Cochrane Library were searched up to 25 November 2018. All articles published in English, German and Scandinavian languages focusing on children and adolescents with JIA and without JIA in relation to oral health measures, were considered. Two authors independently evaluated observational studies for inclusion. The study quality was assessed using modified Newcastle Ottawa Scale. Meta-analysis was performed for studies focusing on dental caries as an outcome. Results Nineteen articles met the inclusion criteria, covering a range of oral diseases/conditions and OHRQoL. Eighteen studies had cross-sectional design. No mean difference of dmft/DMFT indices (decayed/missed/filled teeth) was observed between the JIA - and healthy group. None of the oral health measures including dental erosive wear, enamel defects, dental maturation and OHRQoL, indicated better oral health among children and adolescents with JIA compared to healthy group. However, periodontal conditions and TMD were more predominant among children and adolescents with JIA compared to healthy peers. Conclusions Based on the cross-sectional studies, periodontal diseases and TMD were found to be more frequent in children and adolescents with JIA compared to healthy peers. Furthermore, more high-quality studies with large sample size are needed before we infer any concrete conclusion regarding the association between the prevalence of oral and TMJ diseases or oral conditions in relation to activity and severity of JIA.